Hemocompatibility and cytotoxicity of small-diameter bioabsorbable tissue-engineered vascular grafts depending on anti-thrombogenic and antimicrobial coating - Eugenia O. Krivkina; Elena A. Velikanova; Eugenia A. Senokosova; Maryam Yu. Khanova; Tatyana V. Glushkova; Larisa V. Antonova; Leonid S. Barbarash (Russian Open Medical Journal)
Anti-thrombogenic and antimicrobial coatings of polymer grafts constitute a promising approach to preventing infection and thrombosis of vascular grafts. The objective was to study the hemocompatibility and cytotoxicity of PHBV/PCL grafts with iloprost and amphiphilic coating. Material and Methods — Polymer matrices were manufactured by electrospinning a mixture of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and poly(ε-caprolactone) (PCL) polymers. Several matrices were modified by complexation between polyvinylpyrrolidone (PVP) and cationic amphiphile and/or iloprost. The amphiphile was covalently cross-linked to the surface of other PHBV/PCL matrices. Unmodified PHBV/PCL matrices were used as the control group. Hemocompatibility and cytotoxicity of scaffolds before and after the modification were evaluated. Results — The hemocompatibility assessment revealed that hemolysis degree did not exceed normal values in all types of matrices. The PHBV/PCL/PVP matrices had increased platelet aggregation on the surface of the grafts. Subsequent addition of iloprost and amphiphile resulted in a sevenfold reduction of platelet aggregation. In PHBV/PCL/PVP matrices, the degree of platelet adhesion increased without changing the platelet deformation index values. Iloprost and amphiphilic coating of PHBV/PCL/PVP matrices diminished the number of adhered platelets and platelet deformation index by 1.5 times. The amphiphile, covalently cross-linked to PHBV/PCL matrices, caused a negative effect on the platelet adhesion, aggregation, and deformation index values. Evaluation of cytotoxicity of PHBV/PCL/PVP matrices, coated with iloprost and/or cationic amphiphile, demonstrated a slight decline in the rates of cell growth and proliferation after three days. Moreover, after three days, cell deaths and a sharp drop in the cell index values were noted in PHBV/PCL matrices with covalently cross-linked amphiphile. Conclusion — Iloprost and amphiphilic coating of PHBV/PCL grafts has increased their hemocompatibility. Also, there were no signs of cytotoxicity while using the complexation technique. However, covalently cross-linked amphiphile caused an increase in the cytotoxicity of matrices, which may have been indicative of the negative effect observed in this type of surface modification.